2006
DOI: 10.1108/09513550610704716
|View full text |Cite
|
Sign up to set email alerts
|

Public procurement and EU tendering directives – explaining non‐compliance

Abstract: Purpose-The purpose of this paper is to make a contribution to categorising explanations of non-compliance of EU tendering directives and to report on a survey study to the impact of these reasons on compliance with the directives. Design/methodology/approach-A literature review resulted in a conceptual model and related hypotheses, pointing at four potential reasons for (non-)compliance: the purchaser's familiarity with the rules, the perceived inefficiency, organisational incentives to comply, and the expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
146
1
16

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(178 citation statements)
references
References 22 publications
7
146
1
16
Order By: Relevance
“…De Boer and Telgen (1998) assert that during the early days of the inception of public procurement regulations in The Netherlands, many municipalities could not comply with the regulations because they were not familiar with them. Gelderman et al (2006) confirmed this position in a survey on compliance with EU procurement directives. This study was to confirm whether the reason for non-compliance was the same with that found out in Netherlands, which was nonfamiliarity with the laws and regulations, or otherwise.…”
Section: Institutional Legal Frameworksupporting
confidence: 51%
See 2 more Smart Citations
“…De Boer and Telgen (1998) assert that during the early days of the inception of public procurement regulations in The Netherlands, many municipalities could not comply with the regulations because they were not familiar with them. Gelderman et al (2006) confirmed this position in a survey on compliance with EU procurement directives. This study was to confirm whether the reason for non-compliance was the same with that found out in Netherlands, which was nonfamiliarity with the laws and regulations, or otherwise.…”
Section: Institutional Legal Frameworksupporting
confidence: 51%
“…According to De Boer and Telgen (1998), as quoted by Gelderman et al (2006), one of the factors that cause non-compliance with procurement regulations is the level of familiarity with the regulations. De Boer and Telgen (1998) assert that during the early days of the inception of public procurement regulations in The Netherlands, many municipalities could not comply with the regulations because they were not familiar with them.…”
Section: Institutional Legal Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the fact that the importance of supplier diversity is widely acknowledged in the context of public procurement [25][26][27], and given the importance of different contexts and actors as influencers of supplier diversity practices, the understanding of such actors (e.g., the procurers and suppliers) of supplier diversity is not clear enough and supplier diversity still suffers from problems in implementation. Incidentally, understanding barriers or factors that hinder and challenge the implementation of CSR in an organization plays a major role in achieving sustainable development goals [28].…”
Section: Introductionmentioning
confidence: 99%
“…Cumulatively this leads to the undermining of other regulations and the regulation itself, which can lead to a vicious cycle in which more and more rules are promulgated while public confidence in government regulation lessens and compliance outcomes become worse (Gelderman, Ghijsen, & Brugman, 2006). Public procurement is a regulated process and its ultimate agenda is to ensure that value for money is achieved.…”
Section: Regulatory Compliancementioning
confidence: 99%